IMPLEMENTASI COMMUNITY RELATIONS DALAM PROYEK PENGEMBANGAN RUMAH TURI - Dian Esti Nurati, Ayu Pramayanti, Buddy Riyanto & (Transformasi, 2016)
Type of research is Qualitative. Descriptive with objective to describe implementationscommunity relations in the project development of Rumah Turi. With theory Public Relations,community relations and public attitude. The informant was a Public Relations Rumah Turi, thecommunity and the neighborhood. Engineering data collection i.e., interview, observationand documentation. This research uses triangulation of data as the technique of the validityof the data. The analysis of data used 3 components namely data reduction ofdata display, data and drawing. Research results are Public Relations programs have conductedRumah Turi community realtions But in practice still occurs a difference attitude from thecommunity there are people who support and a lot of citizens who refused to peroyekconstruction of Rumah Turi, factors from the refusal of a citizen is, uneven, less preciseobjectives in the implementation of activities. Communityrelations not planned in structured and undertaken also less socializing so that citizens are notaware of activities that have been dijlankan.Key word: Public Relations, Community Relations, Public Attitude